PECULIARITIES OF INTERNAL MANAGEMENT BELONGING TO THE COMPANY ADMINISTRATOR GOVERNED BY LAW NO. 31/1990 - Carmen TODICĂ (Challenges of the Knowledge Society, 2015)
The management (power) responsibility (internal management) involves committing physical operations of implementing the social will embodied in the General Assembly decisions as well as verifying their execution. In this way, the administrator is authorized by the General Assembly to execute its decisions. Furthermore, these decisions implementation implies concluding legal deeds (of conservation, management and disposal) requested by the activity of the company, and thus, achieve its core business. However, as have emphasized, certain legal deeds of disposition of particular importance to the assets of the company, may be concluded only with the approval of the general meeting of shareholders. In this context, as well as a lacunar regulation on the applicable sanction it is necessary to analyze the effects such the lack of authorization, as well as the administrator liability in relation to the management of the company. These powers (authorities) of the administrator concern the internal management of the company (management),that is the relationships of the manager with the company and shareholders, which requires delineation of the power they represent.